The effects of teacher efficacy, instructional leadership and professional learning communities of student achievement in literacy and numeracy in primary schools within Sibu division - Sio, Jarrod Jyh Lih (2020)
The purpose of this study was to investigate the effects of teacher efficacy (TE),instructional leadership (IL) and professional learning communities (PLC) on studentachievement in literacy and numeracy in primary schools within Sibu division. The main objectiveof this study was to determine if TE, IL and PLC could predict student achievement inliteracy and numeracy. This study utilised the Teacher Self-Efficacy model (Tschannen-Moran,Woolfolk Hoy & Hoy, 1998), the Instructional Leadership model (Hallinger & Murphy, 1985)and Professional Learning Communities model (Hord, 1997). Using the quantitative approach, thedata was collected using questionnaires and was analysed with the Statistical Packages forSocial Sciences. The sample was selected by using stratified random sampling technique involving694 teachers who taught 105 primary schools. Using descriptive statistics, the study observedlevels of practice for TE, IL and PLCs. The differences between gender, teaching experience andacademic qualification were analysed using the t-test and one-way analysis of variance. The studyreported no significant differences in respondent perceptions based on gender and academic qualification for TE, IL and PLC, except for teaching experience vis--vis teacherefficacy. Here, the post hoc Tukey test revealed that efficaciousness grows with experience with F(3, 689) =14.99, p = 0.00. Binary logistic regression was applied to predict theindependent variables influence on student achievement. The findings revealed that a dimensionof instructional leadership (supervising and evaluating instruction) emerged as the best predictorof student achievement for English literacy, with the model explaining between 17.8% (Cox & Rsquared) and 23.9% (Nagelkerke R squared) of the variance in IL. The result indicated that thestudents were more than 17 times more likely to achieve 100% literacy rate for Englishlanguage literacy when the headmaster supervised and evaluated instruction, controlling forall the other factors. In conclusion, supervising and evaluating instruction had a positiveinfluence on students achievement for English language literacy. This study highlyrecommends active supervision and evaluation of instruction as a possible course of action forheadmasters who desire an improved outcomewith regard to English language literacy.